Treason - Doherty, Berlie; Andersen (London : Andersen Press Limited, 2017)
Will Montague is a page to Prince Edward, son of King Henry VIII. As the King's favourite, Will gains many enemies in Court. His enemies convince the King that Will's father has committed treason and he is thrown into Newgate Prison. Will flees Hampton Court and goes into hiding in the back streets of London. Lost and in mortal danger, he is rescued by a poor boy, Nick Drew. Together they must brave imprisonment and death as they embark on a great adventure to set Will's father free.
English.
Keywords: Pages, Medieval -- Juvenile fiction; Treason -- England -- Juvenile fiction